THE LEVEL OF ASSESSMENT IN LISTENING SKILLS OF GRADE A STUDENTS USING A POWER POINT MEDIA AP-PROACH AND AN INTERACTIVE LECTURE MODEL - Yuni Ertinawati; Syahira Mawla Suherman; Fanny Nu Apriliany; Nurul Camilah Rahdianti (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to improve listening skills through the use of Power Point media for students in grade 1-A of Indonesian Language Education, Siliwangi University. This research was conducted online through the Gmeet application to evaluate listening skills and the ability to do student evaluations in grade 12 Indonesian subjects. The research method used is a qualitative descriptive research method. The results showed that of the 5 best students who managed to achieve the highest score in filling out questions, no one achieved 100% success. Technical constraints such as unstable networking, disconnected sound, and less obvious audio are major obstacles in online learning, leaving students unable to work on the problem to the fullest. Although most of the students (72.2%) were able to listen well, 27.8% of students had difficulty. The materials provided include association, metaphor, personification, metonymy, pleonasm, hyperbola, lithotes, euphemism, irony, cinism, and synekdok. Researchers realize that not all students have a strong memory, so the conclusion is that 1-A students majoring in Indonesian Language Education cannot answer quizzes or questions 100% correctly, especially with disturbances during online learning.